How Adult Educators' Positionality Impact the Learners in the Literacy Programs for Foreign Spouses in Taipei County, Taiwan - Jannette Wei-Ting Wang (Adult Education Research Conference, 2014)
The purpose of this qualitative study is to critically examine and explore the “positionalities” including the gender, race and class of adult educators who taught the literacy program of foreign spouses in Taiwan. Furthermore, the effect of positionalities such as gender awareness on a teaching environment will also be studied. The first research question is: How do literacy educators of foreign spouses position themselves and how do they position the new immigrant learners? The second question is: How do literacy educators of foreign spouses teach learners to face the negative stereotypes about them in Taiwan’s society?